SDCBP/Syntenin-1 stabilizes BACH1 by disassembling the SCFFBXO22–BACH1 complex in triple-negative breast cancer - Tran, Phi-Long; Kim, Okhwa; Hwangbo, Cheol; Kim, Hyo-Jin; Kim, Young-Myeong; Lee, Jeong-Hyung (The EMBO journal, 2025)
BACH1 is a redox-sensitive transcription factor facilitating tumor progression in triple-negative breast cancer (TNBC). However, the molecular mechanisms regulating BACH1 function in TNBC remain unclear. In this study, we demonstrate that SDCBP, a tandem-PDZ-domain protein, stabilizes BACH1 by disassembling the Skp1-Cullin1-FBXO22 (SCF FBXO22 )-BACH1 complex via a heme/heme-oxygenase-1-independent manner in TNBC cells. Our data revealed that SDCBP and BACH1 expression show a significant positive correlation in TNBC cells and TNBC patients tumor tissues. Mechanistically, SDCBP via its PDZ1 domain disassembles the SCF FBXO22 –BACH1 complex via its PDZ1 domain, thereby preventing BACH1 K48-linked polyubiquitination and proteasomal degradation. Knocking down SDCBP induces BACH1 degradation and downregulates expressions of BACH1-induced metastatic genes, thereby suppressing tumor progression in mice bearing TNBC tumors. Moreover, depleting SDCBP leads to upregulation of BACH1-repressed electron transport chain (ETC) genes, such as NDUFA4 and COX6B2 , and increases mitochondrial activity, enhancing anti-tumor efficacy of metformin against TNBC both in vitro and in vivo. These data demonstrate a novel alternative mechanism for BACH1 stabilization mediated by SDCBP, implicating the SDCBP-BACH1 axis as a potential target for enhancing ETC inhibitor efficacy in TNBC combinational therapy. Synopsis The redox-sensitive transcription factor BACH1 facilitates breast cancer metastasis, but its molecular upstream control remains unclear. This work identifies adapter protein syndecan-binding protein 1 (SDCBP, syntenin-1) as a BACH1 regulator in triple-negative breast cancer (TNBC) cells, controlling transcription of pro-metastatic and mitochondrial genes. SDCBP and BACH1 are co-expressed in TNBC cells and promote tumor progression. SDCBP stabilizes BACH1 independently of the heme/HO-1 pathway. SDCBP disassembles the E3 ubiquitin ligase SCF FBXO22 -BACH1 complex via its PDZ1 domain. SDCBP-stabilized BACH1 supports expression of pro-metastatic genes, while suppressing expression of mitochondrial ETC genes and decreasing mitochondrial activity in TNBC cells. Targeting SDCBP enhances the anti-tumor efficacy of ETC inhibitors and metformin in a mouse 4T1 breast cancer model. Adapter protein SDCBP stabilizes BACH1 in triple-negative breast cancer cells, thus regulating transcription of pro-metastatic and mitochondrial genes.